A STUDY OF THE USE OF COMPLIMENT ACT IN MOVIE MANUSCRIPTS: A SOCIO-PRAGMATICS APPROACH - ASRI, ATIKA HERNIAN (2007)
This research discusses the use of compliment act in movie manuscript. The objectives of the research are to clarify the linguistics forms of compliments act, the intention, and reason of compliment act. This research is qualitative research. The data are words, phrase, and sentences taken from printed material used movie manuscripts. The sources of data are movie manuscript entitled Titanic, There’s Something About Mary, and Never Been Kissed. The writer uses document method to collect the data. To clarify the form, the writer refers to the linguistic form theory; in clarifying the intention of compliments act the writer employs speech acts theory. The writer applies speaking grid of Hymes to clarify the reason of using compliments. Having analyzed the data, the writer finds that the forms of compliment acts are word, phrase, and sentences. Related to the intention, the writer gets seven kinds of intentions, namely, to insult, to satire, to motivate, to praise, to inform, to respect, and to thank. The reasons of compliment act are to insult, to satire, to inform, to respect, to encourage, to show admiration, to show rapport, and to show positive evaluation